Competency Mapping of Universitas Terbuka’s Early Childhood Teacher Education Graduates: Findings from a Tracer Study - Mahardika, Esti Kurniawati; Amini, Mukti; Ulfah, St. Maria; Novita, Dian; Luluk, Hadiqotul; Saabighoot, Yus Alvar; Djatmiko, Tedjo; Windhi, Ernayanti Nur (Universitas Negeri Makassar, 2025)
The quality of educational institutions is often measured by the competencies of their graduates, especially in teacher education programs. This study aims to evaluate the quality of graduates from the Early Childhood Education (PG-PAUD) program at Universitas Terbuka by assessing the satisfaction of school principals who supervise these alumni. The research addresses the challenge of ensuring that teacher education programs produce graduates equipped with the necessary competencies to meet the demands of early childhood education. Employing a qualitative tracer study approach, data were collected through semi-structured interviews with ten school principals selected purposively based on their direct experience overseeing PG-PAUD UT alumni. The findings reveal that principals generally express satisfaction with the graduates’ performance, highlighting strengths such as high motivation, adaptability, effective communication, and teamwork skills. However, a notable weakness lies in graduates’ ability to utilize assessment data for planning child development, which principals attribute to a broader issue among early childhood educators. These results provide valuable insights for the PG-PAUD program, suggesting the need to enhance curriculum and training focused on assessment literacy and practical application, thereby better preparing future graduates for their professional roles.